Oxygen evolution activity and stability of iridium in acidic media. Part 2. - Electrochemically grown hydrous iridium oxide - Cherevko, Serhiy; Geiger, Simon; Kasian, Olga; Mingers, Andrea; Mayrhofer, Karl (Journal of Electroanalytical Chemistry, 2016)
Hydrous iridium oxide is a well-known material for its electrochromism and electrocatalytic activity, e.g. in oxygen and chlorine evolution reactions ( OER) and (CER). Poor durability during the OER is, however, usually considered as a major drawback. In the current work dissolution of hydrous oxide, prepared from metallic iridium by applying a potential cycle protocol of different number of cydes, has been investigated using a scanning flow cell (SFC) inductively coupled plasma mass spectrometer (ICP-MS) based setup. It is shown that in the potential region preceding the OER, dissolution behavior of such electrodes. is very similar to that of metallic iridium discussed in Part I. It is suggested that at anodic potentials the process is controlled by oxidation of metallic iridium underneath a hydrous oxide, with formation of a thin compact anhydrous oxide layer sandwiched between metal and hydrous oxide. The application of a reductive potential results in the reduction of the compact oxide layer and also leads to dissolution. At these potentials some dissolution of hydrous oxide itself is postulated. Decomposition of iridium (V) oxyhydroxide with formation of molecular oxygen and Ir(III) complexes is suggested at higher anodic potentials during OER. We hypothesize that formation of the soluble Ir(III) complex or complexes and their dissolution is responsible for the observed variation of dissolution with potential in the whole studied potential window. Based on the experimental results and an extended literature overview, a new mechanism of OER triggered dissolution is proposed. The difference in activity and stability of electrochemically prepared hydrous oxides and, usually more stable, "dry" oxides is suggested to be a consequence of different OER mechanisms on these materials. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Iridium hydrous oxide; Iridium dissolution; Corrosion; Degradation; Oxygen evolution